PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA BIMA - Fitrah Ariansyah; Kusumayadi, Firmansyah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
This study aims to determine the effect of work motivation significantly on the work productivity of employees at the Bappeda Office of Bima City. The instrument in this study used a questionnaire with a Likert scale. The population in this study were all employees at the Bima City Bappeda Office, totaling 51 employees, with details of 38 civil servants, 2 honorary k2 workers, and 11 contract workers. The sample in this study were 38 civil servants with a sampling technique using purposive sampling. Data collection techniques using observation, interviews, questionnaires, documentation. The data analysis technique used validity test, reliability test, simple linear regression test, simple correlation coefficient test, coefficient of determination test and t test with the help of SPSS version 22 for windows. The results showed that role ambiguity had a significant effect on employee performance at the Department of Cooperatives, Small and Medium Enterprises, Bima Regency.